2015
DOI: 10.1002/nml.21137
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Determinants of Nonprofit Board Performance

Abstract: There is an increased awareness that the performance of boards (good governance) is not only determined by structural determinants but by behavioral determinants as well. These behavioral determinants might be particularly important for public and nonprofit governance, where the role of the board is more diffuse and heterogeneous than in corporate governance. Here we investigate how social dynamics within boards in secondary education influence their performance. We follow a concise model that includes cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 53 publications
2
25
1
Order By: Relevance
“…Another regularly criticized methodological issue in the research on the FM-Model is the reliance on the CEO as a single respondent in some of the research (Huse, 2009a). The choice of the CEO as the single respondent is often motivated by the difficult accessibility of non-executive board members and justified by stating that the CEO is the only person that can properly assess both the ins and outs of the organization as well as the functioning of the board of directors (Minichilli et al, 2012;Heemskerk et al, 2015). Contrary to our hypotheses, the moderator model comparing studies that relied on the CEO as single respondent with studies that relied on other or multiple respondents was not significant.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Another regularly criticized methodological issue in the research on the FM-Model is the reliance on the CEO as a single respondent in some of the research (Huse, 2009a). The choice of the CEO as the single respondent is often motivated by the difficult accessibility of non-executive board members and justified by stating that the CEO is the only person that can properly assess both the ins and outs of the organization as well as the functioning of the board of directors (Minichilli et al, 2012;Heemskerk et al, 2015). Contrary to our hypotheses, the moderator model comparing studies that relied on the CEO as single respondent with studies that relied on other or multiple respondents was not significant.…”
Section: Discussioncontrasting
confidence: 60%
“…This further underlines the severe differences in findings between studies and makes it hard to draw conclusions. Some empirical studies have found that the impact of cognitive conflict depends on the board task and have suggested that cognitive conflict has a more positive impact on the service task of a board than on its control task (Zattoni et al, 2015, Heemskerk et al 2015. However, the similarities found in the meta-analysis for the effect on board control task performance, and board service task performance does not support this supposition.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Corporate governance mechanisms should be enhanced in these transformed banks to improve the composition of the board and appoint experienced CEOs. An increase in monitoring and control tasks can help to improve organizational effectiveness and performance (Cumberland et al ; Heemskerk, Heemskerk, and Wats ). Following Shaw and Allen (), we consider that the initial social mission of savings banks should have been maintained with a more heavy‐handed business management model.…”
Section: Discussionmentioning
confidence: 99%
“…This research contributes to, and further validates, how board affective conflict is perceived in the boardroom regarding its negative consequences. However, it is useful to note that avoiding this form of conflict paradoxically could hinder good governance (Heemskerk et al, 2016).…”
Section: Affective Conflictmentioning
confidence: 99%